Curing agent as well as preparation method and application thereof
By using coal-based solid waste such as desulfurization gypsum and fly ash in the curing agent, as well as glass fiber, carbon fiber and alkali exciters, an efficient gelling reaction is formed, which solves the problem of insufficient performance of coal-based solid waste storage and cement-based concrete materials, and achieves a low-cost and high-performance concrete curing agent.
Patent Information
- Application Number
- CN202411685286.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, the large-scale storage of desulfurization gypsum and fly ash by-products of coal-fired power generation leads to problems of land resource occupation and environmental pollution, as well as problems of high costs, serious pollution, and poor tensile strength and durability in the preparation process of cement-based concrete materials.
A curing agent is provided, and its raw materials include desulfurization gypsum, fly ash, cement, quicklime, glass fiber, carbon fiber and alkali exciter. By precisely controlling the content and types of mixed fibers and alkali exciters, an efficient gelling reaction is formed, which significantly enhances the consolidation ability of the curing agent.
It effectively solves the problem of large-scale storage of desulfurization gypsum and fly ash, reduces the production cost of curing agents, and greatly improves the tensile strength and durability of concrete, providing a green, economical and high-performance solution for the construction industry.
Smart Images

Figure BDA0005149266230000111 
Figure BDA0005149266230000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and in particular to a curing agent, a preparation method and application thereof. Background Art
[0002] In the current energy consumption structure, coal still occupies a dominant position, especially in the power generation industry. The large amount of coal-generated byproducts such as desulfurized gypsum and fly ash has become a major challenge in the field of environmental protection. The annual output of desulfurized gypsum and fly ash is large. If these coal-based solid wastes are not used reasonably, they will not only occupy a large amount of land resources, but also may cause environmental problems such as water pollution and air pollution, posing a threat to ecological balance and human health.
[0003] With the acceleration of urbanization, the demand for the construction industry and infrastructure construction has exploded, and the demand for building materials such as concrete has also surged. Traditional cement-based concrete occupies an important position in the construction field with its excellent mechanical properties. However, the cement production process has high energy consumption and large carbon emissions, and the production cost of concrete is greatly affected by the price of cement, which to a certain extent restricts the sustainable development of the construction industry. In addition, the cement curing agent has limited effect on the reinforcement of concrete, especially the durability problem in extreme environments, and better solutions are still needed.
[0004] Therefore, how to effectively utilize coal-based solid wastes such as desulfurized gypsum and fly ash to develop a low-cost, environmentally friendly new curing agent to improve the tensile strength and durability of concrete materials has become a key issue that needs to be urgently addressed in this field. Summary of the invention
[0005] The main purpose of the present invention is to provide a curing agent, a preparation method and application thereof, so as to solve the problems of land resource occupation and environmental pollution caused by the large-scale storage of desulfurization gypsum and fly ash, by-products of coal-fired power generation in the prior art, and the problems of high cost, serious pollution, poor tensile strength and durability in the preparation process of cement-based concrete materials.
[0006] In order to achieve the above object, according to one aspect of the present invention, a curing agent is provided. The raw materials include base material, mixed fiber, alkali activator and water, the base material includes desulfurized gypsum, fly ash, cement and quicklime, wherein the weight ratio of the mixed fiber to the base material is (1.2-2.4):100, and the weight ratio of the alkali activator to the base material is (8-16):100; the mixed fiber includes glass fiber and carbon fiber; the alkali activator includes one or more of sodium carbonate solution, sodium silicate solution and sodium hydroxide solution.
[0007] Further, in the mixed fiber, the weight ratio of glass fiber to carbon fiber is (0.8-2):1, preferably, the weight ratio of glass fiber to carbon fiber is (1.2-1.6):1; and / or, the aspect ratio of glass fiber is (100-300):1, the length of glass fiber is 5-10 mm, and the diameter is 0.01-0.03 mm; and / or, the aspect ratio of carbon fiber is (200-400):1, the length of carbon fiber is 2-4 mm, and the diameter is 0.005-0.01 mm; preferably, the glass fiber is first pretreated by one or more of heat treatment, alkali washing and surfactant treatment; more preferably, the heat treatment temperature is 400-600°C, and the time is 0.5 ~2.0h; more preferably, one or more of sodium hydroxide solution, potassium hydroxide solution and sodium carbonate solution are used for alkali washing; more preferably, one or more of titanate coupling agent, fluorocarbon compound and polyacrylamide are used for surfactant treatment; preferably, the carbon fiber is subjected to a second pretreatment by one or more of pre-oxidation, resin impregnation and acid washing; more preferably, the pre-oxidation atmosphere includes one or more of air, oxygen and ozone, the temperature is 200~400℃, and the time is 1.0~2.5h; more preferably, one or more of epoxy resin, polyimide resin and phenolic resin are used for resin impregnation; more preferably, one or more of sulfuric acid, nitric acid and hydrochloric acid are used for acid washing.
[0008] Furthermore, the alkaline activator is a mixture of a sodium silicate solution and a sodium carbonate solution, wherein the weight ratio of sodium silicate to sodium carbonate is (0.5-2.5):1; preferably (1-2):1.
[0009] Furthermore, the moisture content of the desulfurized gypsum is ≤15% by weight; and / or the content of CaSO4·2H2O in the desulfurized gypsum is ≥90% by weight; and / or, in the fly ash, Al2O3 accounts for 30-40%, SiO2 accounts for 45-55%, and Fe2O3 accounts for 1.5-10% by weight.
[0010] Furthermore, the cement includes one or more of silicate cement, sulphoaluminate cement and aluminate cement; and / or the weight percentage of CaO in the quicklime is ≥80%; and / or the particle size of the quicklime is 50-200 μm.
[0011] Furthermore, in terms of weight percentage, the weight ratio of desulfurized gypsum, fly ash, cement and quicklime in the base material is (25-35): (20-30): (10-20): (8-12); and / or the weight ratio of mixed fiber to base material is (1.6-2.0): 100; and / or the weight ratio of alkali activator to base material is (10-15): 100; and / or the weight ratio of water to base material is (35-55): 100, preferably (40-50): 100.
[0012] According to another aspect of the present invention, a method for preparing the above-mentioned curing agent is provided, comprising the following steps: step S1, performing a first mixing of desulfurized gypsum, fly ash, cement, quicklime, and mixed fiber to obtain a first mixture; step S2, performing a second mixing of the first mixture and water to obtain a second mixture; step S3, performing a third mixing of the second mixture and an alkali activator to obtain a curing agent.
[0013] Further, the first mixing speed is 600-800 rpm, and the time is 2-10 min; and / or, the second mixing speed is 300-500 rpm, and the time is 3-8 min; and / or, the third mixing speed is 400-600 rpm, and the time is 5-10 min.
[0014] Furthermore, before performing step S1, the preparation method further comprises the step of drying the desulfurized gypsum until the weight percentage of water in the desulfurized gypsum is ≤5%; and / or, before performing step S1, the preparation method further comprises grinding the fly ash until the specific surface area of the fly ash is 300 to 500 m 2 / g, particle size D90≤50μm.
[0015] According to another aspect of the present invention, there is provided use of the above-mentioned curing agent in the field of construction.
[0016] By applying the technical solution of the present invention, the composition of the curing agent, especially the content and type of the mixed fiber and the alkali activator, is precisely controlled, and the problem of large-scale stockpiling of fly ash and desulfurized gypsum is effectively solved, the production cost of the curing agent is reduced, and the tensile strength and durability of the concrete are greatly improved, providing a green, economical, high-performance solution for the construction industry, which has broad application prospects and significant environmental benefits. DETAILED DESCRIPTION
[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0018] As described in the background of the present invention, the prior art has the problems of land resource occupation and environmental pollution caused by the large-scale storage of desulfurized gypsum and fly ash, by-products of coal-fired power generation, and the problems of high cost, serious pollution, poor tensile strength and durability in the preparation process of cement-based concrete materials. In order to solve the above problems, in a typical embodiment of the present invention, a curing agent is provided, the raw materials include base material, mixed fiber, alkali activator and water, the base material includes desulfurized gypsum, fly ash, cement and quicklime, wherein, in the raw materials, the weight ratio of mixed fiber to base material is (1.2-2.4):100, and the weight ratio of alkali activator to base material is (8-16):100; the mixed fiber includes glass fiber and carbon fiber; the alkali activator includes one or more of sodium carbonate solution, sodium silicate solution and sodium hydroxide solution.
[0019] The raw materials of the curing agent of the present application include desulfurized gypsum, fly ash, cement, quicklime, mixed fiber, alkali activator and water. Among them, desulfurized gypsum and fly ash play the main skeleton role in the curing agent of the present application. Desulfurized gypsum has good gelling properties because it is rich in calcium sulfate (CaSO4·2H2O), and fly ash can react in an alkaline environment because it contains a large amount of active silicon and aluminum components. Under the action of the alkali activator, the two can undergo hydration reaction and volcanic ash reaction to generate products with high gelling activity, thereby significantly enhancing the consolidation ability of the curing agent.
[0020] In addition, by using the byproducts (desulfurized gypsum and fly ash) in the coal-fired power generation process as the raw materials of the curing agent, it can also effectively solve the environmental pollution and land resource occupation problems caused by the large-scale storage of desulfurized gypsum and fly ash, and realize the recycling of resources. Secondly, the addition of cement and quicklime can also enhance the gelling properties of the curing agent. As a cementing material, the hydration reaction of cement can significantly improve the strength and stability of the curing agent; the calcium hydroxide generated when quicklime reacts with water can stimulate the activity of desulfurized gypsum and fly ash and enhance the early strength of the curing agent. The synergistic effect of the two with desulfurized gypsum and fly ash is conducive to significantly improving the comprehensive performance of the curing agent, while reducing the demand for traditional cement and reducing production costs.
[0021] In addition, the curing agent of the present application particularly includes hybrid fibers, which form a three-dimensional network structure in concrete, which can effectively disperse stress and reduce the generation of cracks, thereby improving the reinforcing effect of the curing agent on the tensile strength of concrete. In addition, the addition of fibers can also improve the durability of the curing agent, so that it can still maintain excellent tensile strength and toughness in a complex environment. It should be noted that the application specifically limits the types of hybrid fibers. Among them, glass fiber has excellent tensile strength and corrosion resistance, which can significantly enhance the crack resistance and toughness of the curing agent; carbon fiber has extremely high strength and lightweight characteristics, which can significantly improve the tensile strength and structural stability of the curing agent.
[0022] In addition, the alkali activator plays a key role in stimulating the active ingredients of desulfurized gypsum and fly ash. The alkaline environment can accelerate the hydration reaction and promote the formation of aluminosilicates, thereby significantly enhancing the gelling ability of the curing agent. Moreover, the use of an alkali activator can reduce the amount of cement used, reduce energy consumption and carbon emissions in the production process, and has significant environmental benefits. It should be noted that the present application specifically limits the types of alkali activators, wherein sodium carbonate solution and / or sodium hydroxide solution can provide a sufficient alkaline environment to promote the dissolution of active silicon and aluminum components in fly ash and desulfurized gypsum and participate in the hydration reaction, thereby accelerating the reaction process and improving the early strength of the curing agent. While providing alkaline conditions, the sodium silicate solution reacts with the active ingredients to generate a silicate gelling substance with higher strength, further enhancing the bonding force and long-term durability of the curing agent.
[0023] Moreover, in the raw materials of the curing agent of the present application, the mixed fiber and the alkali activator work synergistically. In an alkaline environment, the mixed fiber can be effectively dispersed in the curing agent to form a uniformly distributed reinforced network structure, which significantly improves the comprehensive mechanical properties of the curing agent. The alkali activator not only effectively stimulates the activity of fly ash and desulfurized gypsum, but also promotes the uniform distribution of the fiber in the curing agent by improving the fluidity of the mixed system, and enhances the bonding force between the fiber and the gelling material, thereby achieving a dual improvement in the strength and durability of the curing agent.
[0024] At the same time, the present application also defines the dosage of mixed fibers and alkali activators in the curing agent raw materials. The mixed fibers with the above dosage can be evenly dispersed in the curing agent to avoid fiber agglomeration due to too high dosage, or the inability to fully exert the reinforcing effect due to too low dosage. In addition, the physical and chemical bonding formed between the mixed fibers and the hydration products of desulfurized gypsum and fly ash is conducive to enhancing the microstructural stability of the curing agent, so that it performs better when subjected to complex stress conditions. The alkali activator with the above dosage can not only provide a sufficient alkaline environment to promote the activation of fly ash and desulfurized gypsum and accelerate the hydration reaction, but also effectively avoid excessive use, preventing the curing agent from decreasing performance or increasing costs.
[0025] In summary, this application effectively solves the problem of large-scale stockpiling of fly ash and desulfurized gypsum by controlling the composition of the curing agent, especially the dosage and type of the mixed fiber and alkali activator, reduces the production cost of the curing agent, and greatly improves the tensile strength and durability of the concrete, providing a green, economical, high-performance solution for the construction industry, with broad application prospects and significant environmental benefits.
[0026] In a preferred embodiment, in the mixed fiber, the weight ratio of glass fiber to carbon fiber is (0.8-2):1, preferably, the weight ratio of glass fiber to carbon fiber is (1.2-1.6):1; and / or, the aspect ratio of glass fiber is (100-300):1, the length of glass fiber is 5-10 mm, and the diameter is 0.01-0.03 mm; and / or, the aspect ratio of carbon fiber is (200-400):1, the length of carbon fiber is 2-4 mm, and the diameter is 0.005-0.01 mm. Under the above conditions, the tensile strength and toughness of the curing agent can be further enhanced, its microstructure can be optimized, the formation of pores and cracks can be reduced, and the stress generated during the curing process can be effectively dispersed, which significantly reduces the risk of cracking of the curing agent. Moreover, while ensuring that the curing agent has good tensile strength and toughness, its compressive properties and structural integrity can also be taken into account.
[0027] In order to further enhance the fiber surface activity, reduce the agglomeration of fibers, improve the bonding between the mixed fibers and the curing agent base material, optimize the microstructure of the curing agent, improve the strength, toughness and durability of the curing agent, and reduce the fiber dosage to reduce costs, in a preferred embodiment, the glass fiber and the carbon fiber are also pretreated. Preferably, the glass fiber is first pretreated by one or more of heat treatment, alkali washing and surfactant treatment; more preferably, the heat treatment temperature is 400-600°C and the time is 0.5-2h; more preferably, sodium hydroxide solution, potassium hydroxide solution and sodium carbonate are used. Preferably, the carbon fiber is subjected to a second pretreatment by one or more of pre-oxidation, resin impregnation and acid washing; More preferably, the pre-oxidation atmosphere comprises one or more of air, oxygen and ozone, the temperature is 200-400°C, and the time is 1-2.5h; More preferably, the resin is impregnated with one or more of epoxy resin, polyimide resin and phenolic resin; More preferably, the acid washing is carried out with one or more of sulfuric acid, nitric acid and hydrochloric acid.
[0028] The inventors further optimized the composition of the alkaline activator. In a preferred embodiment, the alkaline activator is a mixture of sodium silicate solution and sodium carbonate solution, wherein the weight ratio of sodium silicate to sodium carbonate is (0.5-2.5):1; preferably (1-2):1. Under the above conditions, the hydration reaction can be further accelerated to generate a stable CSH gel, and the desulfurized gypsum and fly ash products can form a dense network structure, which can significantly improve the early strength and long-term durability of the curing agent, optimize its microstructure, enhance its anti-seepage and anti-corrosion capabilities, realize the resource utilization of coal-fired byproducts, and reduce costs.
[0029] In a preferred embodiment, the desulfurized gypsum includes desulfurized gypsum from a coal-fired power plant; preferably, the moisture content of the desulfurized gypsum is ≤15% by weight; and / or, preferably, the content of CaSO4·2H2O in the desulfurized gypsum is ≥90% by weight; and / or, the fly ash includes fly ash from a coal-fired power plant; preferably, in the fly ash, Al2O3 accounts for 30-40%, SiO2 accounts for 45-55%, and Fe2O3 accounts for 1.5-10% by weight. Under the above conditions, the desulfurized gypsum and the fly ash can more fully exert their synergistic effect, significantly enhance the hydration activity and strength of the curing agent, optimize its microstructure, reduce porosity, and improve durability.
[0030] In order to further promote the hydration and gelling reaction of desulfurized gypsum and fly ash, optimize the microstructure of the curing agent, enhance its early mechanical properties and long-term durability, and more effectively reduce the production cost, in a preferred embodiment, the cement includes one or more of silicate cement, sulphoaluminate cement and aluminate cement; and / or the weight percentage of CaO in the quicklime is ≥80%; and / or the particle size of the quicklime is 50 to 200 μm.
[0031] In a preferred embodiment, in the base material, the weight ratio of desulfurized gypsum, fly ash, cement and quicklime is (25-35): (20-30): (10-20): (8-12) by weight percentage. Desulfurized gypsum and fly ash in the above ratio can more efficiently undergo hydration and pozzolanic reaction through the catalytic action of the alkali activator to generate gelling active products, which form a dense hydration network at the microscopic level, thereby significantly improving the mechanical properties of the curing agent. Cement and quicklime in the above range can not only provide additional gelling properties, but also synergize with the reaction products of desulfurized gypsum and fly ash to form a more stable hydration structure, further enhancing the mechanical properties of the curing agent.
[0032] In a preferred embodiment, the weight ratio of the mixed fiber to the base material is (1.6-2):100; and / or, the weight ratio of the alkali activator to the base material is (10-15):100; and / or, the weight ratio of water to the base material is (35-55):100, preferably (40-50):100. Under the above conditions, the synergistic effect of each component can more significantly improve the mechanical properties and durability of the curing agent, optimize the material structure and production cost, promote the resource utilization of coal combustion by-products, reduce environmental pressure, and provide the construction industry with a high-performance, low-cost, and environmentally friendly new curing agent solution, especially in improving crack resistance and reducing production energy consumption.
[0033] In another typical embodiment of the present invention, a method for preparing the above-mentioned curing agent is also provided, comprising the following steps: step S1, performing a first mixing of desulfurized gypsum, fly ash, cement, quicklime, and mixed fiber to obtain a first mixture; step S2, performing a second mixing of the first mixture and water to obtain a second mixture; step S3, performing a third mixing of the second mixture and an alkali activator to obtain a curing agent.
[0034] In the preparation method of the present application, first, desulfurized gypsum, fly ash, cement, quicklime and mixed fiber are preliminarily mixed to form a first mixture, so as to achieve physical dispersion and preliminary contact between the components and create a uniform raw material environment for subsequent chemical reactions; then, the first mixture is mixed with water for a second time, and the quicklime undergoes a rapid hydration reaction when it meets water and releases a large amount of heat, which accelerates the hydration process of the material, promotes the dissolution and diffusion of various components, and forms a stable second mixture; finally, the second mixture is mixed with an alkaline activator for a third time, and the alkaline environment can effectively stimulate the potential active components in the desulfurized gypsum and fly ash, promote the gelling reaction, and finally generate a high-strength curing agent.
[0035] The preparation method of the present application can optimize the microstructure of the curing agent, enhance its mechanical properties and durability, reduce production costs, effectively address the problem of coal by-product treatment, and promote the development of green building materials technology, especially in improving the environmental adaptability and economic benefits of the curing agent.
[0036] In order to make the components mixed more evenly, further improve the production efficiency, and enhance the mechanical properties and durability of the curing agent, in a preferred embodiment, the rotation speed of the first mixing is 600-800 rpm, and the time is 2-10 min; and / or, the rotation speed of the second mixing is 300-500 rpm, and the time is 3-8 min; and / or, the rotation speed of the third mixing is 400-600 rpm, and the time is 5-10 min.
[0037] In a preferred embodiment, before performing step S1, the preparation method further comprises the step of drying the desulfurized gypsum until the weight percentage of water in the desulfurized gypsum is ≤5%. Under the above conditions, the problem of curing agent performance degradation caused by excessive water during the hydration reaction can be more effectively avoided, the activity of the desulfurized gypsum can be further enhanced, and the mechanical properties and long-term stability of the curing agent can be improved.
[0038] In a preferred embodiment, before performing step S1, the preparation method further comprises grinding the fly ash to a specific surface area of 300 to 500 m 2 / g, particle size D90≤50μm. Under the above conditions, the specific surface area of fly ash can be significantly increased, the reaction activity can be enhanced, the hydration reaction and gelation of fly ash with desulfurized gypsum, cement and other components can be promoted, and the microscopic pore structure of the curing agent can be optimized, thereby enhancing its early strength and long-term durability.
[0039] Preferably, in step S1, desulfurized gypsum, fly ash, cement and quicklime are first mixed with glass fiber for the fourth time, and then mixed with carbon fiber for the fifth time. This step-by-step mixing strategy can more effectively regulate the dispersion state and bonding effect of fiber. First, due to the difference in physical properties between glass fiber and carbon fiber, step-by-step mixing helps to ensure that each fiber can be evenly distributed in the solid matrix raw material, and the fiber agglomeration phenomenon can be effectively avoided, thereby ensuring the uniformity of the microstructure of the curing agent and improving its mechanical properties. Secondly, the preliminary mixing of inorganic materials such as quicklime, cement and glass fiber provides a more stable base material environment for the subsequent addition of carbon fiber, which can promote the formation of chemical bonds between fiber and matrix, and further enhance the tensile strength and toughness of the curing agent. Optimizing its mixing order can not only further improve the structural stability and comprehensive performance of the curing agent, reduce energy consumption and cost in the production process, but also effectively solve the problem of uneven fiber distribution and weak matrix-fiber combination in the preparation process of traditional curing agent, improve resource utilization efficiency, and reduce environmental pollution.
[0040] In another typical embodiment of the present invention, the application of the above-mentioned curing agent in the field of construction is also provided. As mentioned above, the curing agent of the present application has excellent mechanical properties and durability. When it is used in the field of construction, it can significantly improve the safety and service life of the building structure and reduce the cost of later maintenance. Secondly, the curing agent of the present application utilizes the characteristics of coal-fired byproducts (desulfurized gypsum and fly ash) as resources, effectively solves the problem of handling a large number of industrial solid wastes, reduces pollution to the environment, and conforms to the concept of green building and sustainable development. Furthermore, the building materials prepared using the curing agent of the present application have low production costs and significant economic benefits. In addition, the curing agent has strong environmental adaptability, can maintain stable performance under different climatic conditions, and expands its application range in the construction industry. Its production process has low energy consumption, reduces carbon dioxide emissions, and has a positive driving effect on realizing the low-carbon and environmentally friendly transformation of the construction industry.
[0041] In summary, the application of the curing agent of the present application in the construction field not only improves the building quality and reduces the construction cost, but also promotes the resource utilization of industrial solid waste, promotes the green upgrade of the building materials industry, and has a far-reaching impact on solving the technical, environmental and economic problems existing in traditional building materials.
[0042] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0043] Example 1
[0044] The raw materials of the curing agent include base material, mixed fiber, alkali activator and water in a weight ratio of 100:1.8:12:45, and the base material includes desulfurized gypsum, fly ash, cement and quicklime in a weight ratio of 30:25:15:10.
[0045] The moisture content of desulfurized gypsum is 12%, and the weight percentage of CaSO4·2H2O is 92%; the fly ash includes 35.51% Al2O3, 53.84% SiO2 and 2.79% Fe2O3; the cement is silicate cement with the model of PO 42.5; the weight percentage of CaO in quicklime is 85%, the particle size of quicklime is 90μm, and the model is CL 90-QP; the mixed fiber includes glass fiber (length is 6mm, diameter is 0.03mm, and aspect ratio is 200) and carbon fiber (length is 3mm, diameter is 0.01mm, and aspect ratio is 300) with a weight ratio of 1.4:1. Among them, at 120°C, the glass fiber was pretreated with a sodium hydroxide solution with a mass concentration of 5%; at 150°C, the carbon fiber was pretreated with an epoxy resin; the alkali activator was a mixture of a sodium silicate solution and a sodium carbonate solution, wherein the weight ratio of sodium silicate to sodium carbonate was 1.5:1.
[0046] The preparation method of the curing agent comprises the following steps:
[0047] Step S1: firstly dry the desulfurized gypsum to control the weight percentage of water in the desulfurized gypsum to be less than 5%, and grind the fly ash until the specific surface area of the fly ash is 400m 2 / g, and the particle size D90 is about 50μm; then the desulfurized gypsum, fly ash, cement, quicklime and glass fiber are mixed at 700rpm for 5min, and then the carbon fiber is added and mixed at 700rpm for 3min to obtain a first mixture;
[0048] Step S2, mixing the first mixture with water at 400 rpm for 6 min to obtain a second mixture,
[0049] Step S3, mixing the second mixture with the alkaline activator at 500 rpm for 8 minutes to obtain a curing agent.
[0050] The obtained curing agent is used to prepare cement-based concrete materials.
[0051] Example 2
[0052] The only difference from Example 1 is:
[0053] The glass fiber was heat treated in an air atmosphere furnace at 500°C for 1 hour for pretreatment, and the carbon fiber was pre-oxidized in air at 250°C for 1.5 hours for pretreatment. In the mixed fiber, the weight ratio of glass fiber (length 5 mm, diameter 0.02 mm, aspect ratio 250) and carbon fiber (length 2 mm, diameter 0.01 mm, aspect ratio 200) was 1.2:1.
[0054] Example 3
[0055] The only difference from Example 1 is:
[0056] The glass fiber was oxidized in a potassium permanganate solution at 80°C, and then pretreated by immersing it in isopropyl triisostearate titanate at 60°C for 1.5 hours; the carbon fiber was pickled with sulfuric acid at a mass concentration of 1.5% at 80°C for 2 hours. In the mixed fiber, the weight ratio of glass fiber (length 9 mm, diameter 0.03 mm, aspect ratio 300) and carbon fiber (length 4 mm, diameter 0.01 mm, aspect ratio 400) was 1.6:1.
[0057] Example 4
[0058] The only difference from Example 1 is:
[0059] The alkali activator is a mixture of a sodium silicate solution and a sodium carbonate solution, wherein the weight ratio of the sodium silicate to the sodium carbonate is 1:1.
[0060] Example 5
[0061] The only difference from Example 1 is:
[0062] The alkaline activator is a mixture of a sodium silicate solution and a sodium carbonate solution, wherein the weight ratio of the sodium silicate to the sodium carbonate is 2:1.
[0063] Example 6
[0064] The only difference from Example 1 is:
[0065] The moisture content of desulfurized gypsum is 10%, and the weight percentage of CaSO4·2H2O is 90%; in fly ash, Al2O3 accounts for 30%, SiO2 accounts for 55%, Fe2O3 accounts for 10%, and other impurity components are also included.
[0066] Example 7
[0067] The only difference from Example 1 is:
[0068] The moisture content of desulfurized gypsum is 15%, and the weight percentage of CaSO4·2H2O is 93%; in fly ash, Al2O3 accounts for 40%, SiO2 accounts for 45%, Fe2O3 accounts for 1.5%, and other impurity components are also included.
[0069] Example 8
[0070] The only difference from Example 1 is:
[0071] The cement model is Shili brand R·SAC42.5 grade rapid hardening sulphoaluminate cement (from Dengdian Group Cement Co., Ltd.);
[0072] The weight percentage of CaO in the quicklime is 80%, the particle size of the quicklime is 50 μm, and the model is CL 85-QP.
[0073] Example 9
[0074] The only difference from Example 1 is:
[0075] The cement model is Shili brand CA50 aluminate cement (from Dengdian Group Cement Co., Ltd.);
[0076] The weight percentage of CaO in the quicklime is 90%, the particle size of the quicklime is 150 μm, and the model is CL 90-QP.
[0077] Example 10
[0078] The only difference from Example 1 is:
[0079] Among the raw materials of the curing agent, the weight ratio of the base material, the mixed fiber, the alkali activator and water is 100:1.2:16:55. Among the alkali activator, the weight ratio of sodium silicate to sodium carbonate is 0.5:1. Among the mixed fiber, the weight ratio of glass fiber to carbon fiber is 0.8:1.
[0080] Embodiment 11
[0081] The only difference from Example 1 is:
[0082] Among the raw materials of the curing agent, the weight ratio of the base material, the mixed fiber, the alkali activator and water is 100:2.4:8:35. Among the alkali activator, the weight ratio of sodium silicate to sodium carbonate is 2.5:1. Among the mixed fiber, the weight ratio of glass fiber to carbon fiber is 2:1.
[0083] Example 12
[0084] The only difference from Example 1 is:
[0085] Among the raw materials of the curing agent, the weight ratio of the base material, mixed fiber, alkali activator and water is 100:2:15:50, and the weight ratio of desulfurized gypsum, fly ash, cement and quicklime in the base material is 25:30:10:12.
[0086] Embodiment 13
[0087] The only difference from Example 1 is:
[0088] Among the raw materials of the curing agent, the weight ratio of the base material, mixed fiber, alkali activator and water is 100:1.6:10:40, and the weight ratio of desulfurized gypsum, fly ash, cement and quicklime in the base material is 35:20:20:8.
[0089] Embodiment 14
[0090] The only difference from Example 1 is:
[0091] The preparation method of the curing agent comprises the following steps:
[0092] Step S1: firstly dry the desulfurized gypsum to control the weight percentage of water in the desulfurized gypsum to be less than 5%, and grind the fly ash until the specific surface area of the fly ash is 300m 2 / g, and the particle size D90 is about 50μm; then the desulfurized gypsum, fly ash, cement, quicklime and glass fiber are mixed at 600rpm for 6min, and then the carbon fiber is added and mixed at 600rpm for 4min to obtain a first mixture;
[0093] Step S2, mixing the first mixture with water at 500 rpm for 3 min to obtain a second mixture,
[0094] Step S3, mixing the second mixture with the alkaline activator at 400 rpm for 10 minutes to obtain a curing agent.
[0095] Embodiment 15
[0096] The only difference from Example 1 is:
[0097] The preparation method of the curing agent comprises the following steps:
[0098] Step S1: firstly dry the desulfurized gypsum to control the weight percentage of water in the desulfurized gypsum to be less than 5%, and grind the fly ash until the specific surface area of the fly ash is 500m 2 / g, and the particle size D90 is about 50μm; then the desulfurized gypsum, fly ash, cement, quicklime and glass fiber are mixed at 800rpm for 4min, and then the carbon fiber is added and mixed at 800rpm for 2min to obtain a first mixture;
[0099] Step S2, mixing the first mixture with water at 300 rpm for 8 min to obtain a second mixture,
[0100] Step S3, mixing the second mixture with the alkaline activator at 600 rpm for 5 minutes to obtain a curing agent.
[0101] Comparative Example 1
[0102] The only difference from Example 1 is that no mixed fibers are included.
[0103] By comparison, it can be seen that compared with Example 1, this example does not include mixed fibers. Due to the lack of the reinforcement mechanism of the mixed fibers and the good bonding effect between the fibers and cement, a three-dimensional network structure cannot be formed in the curing agent, resulting in lower tensile strength and toughness, poorer mechanical properties and durability, and a higher risk of cracking.
[0104] Comparative Example 2
[0105] The only difference from Example 1 is that no base activator is included.
[0106] By comparison, it can be seen that compared with Example 1, this example does not include an alkali activator. Due to the lack of the excitation catalytic effect of the alkali activator, the activity of the desulfurized gypsum and the fly ash cannot be fully stimulated during the preparation of the curing agent, resulting in incomplete hydration reaction, less hydration products generated, and the internal microstructure of the material is not tight enough, resulting in the deterioration of the mechanical properties and durability of the curing agent.
[0107] Comparative Example 3
[0108] The only difference from Example 1 is that the alkaline activator is a potassium silicate solution.
[0109] By comparison, it can be seen that the mixture of sodium silicate solution and sodium carbonate solution used as the alkali activator in Example 1 can enhance the activity of the alkali-activated reaction and the stability of the product, form a denser structure, and significantly improve the mechanical properties and durability of the curing agent, while reducing production costs and environmental impacts, compared with a single potassium silicate solution.
[0110] Comparative Example 4
[0111] The only difference from Example 1 is:
[0112] Among the raw materials of the curing agent, the weight ratio of the base material, mixed fiber, alkali activator and water is 100:5:5:30, among the base material, the weight ratio of desulfurized gypsum, fly ash, cement and quicklime is 30:25:15:10, and among the mixed fiber, the weight ratio of glass fiber to carbon fiber is 2:1.
[0113] By comparison, it can be seen that compared with Example 1, the mixed fiber dosage in this case is too much, resulting in uneven fiber dispersion, affecting the full reaction of the alkali activator with the raw materials; the alkali activator dosage is too little, which cannot fully stimulate the activity of the raw materials, resulting in incomplete hydration reaction; at the same time, too low water content will make the mixture too dry, affecting the pouring and the microstructure of the curing agent, and ultimately resulting in poor mechanical properties and durability of the curing agent.
[0114] Comparative Example 5
[0115] The only difference from Example 1 is:
[0116] Among the raw materials of the curing agent, the weight ratio of the base material, mixed fiber, alkali activator and water is 100:0.6:20:60, among the base material, the weight ratio of desulfurized gypsum, fly ash, cement and quicklime is 30:25:15:10, and among the mixed fiber, the weight ratio of glass fiber to carbon fiber is 2.5:1.
[0117] By comparison, it can be seen that compared with Example 1, the mixed fiber dosage of this comparative example is too low, resulting in uneven distribution of fibers in the base material and failure to fully exert the reinforcement effect; the alkali activator dosage of this example is too high, causing a violent hydration reaction, generating excessive heat and gas, destroying the microstructure of the curing agent, and increasing the cost; the water-to-binder ratio of this example is too high, resulting in excessive shrinkage of the curing agent during the hardening process, generating cracks, and affecting the mechanical strength and durability of the curing agent.
[0118] Comparative Example 6
[0119] The only difference from Example 1 is:
[0120] The curing agent raw materials do not include mixed fiber and alkali activator, and only desulfurized gypsum, fly ash, cement and quicklime (the weight ratio is the same as that in Example 1) are used.
[0121] By comparison, it can be seen that compared with this example, Example 1 introduces a mixed fiber material and pretreats it, so that the fibers are evenly distributed in the base material and tightly combined with it to form a network structure, thereby improving the material's crack resistance and durability; at the same time, the addition of an alkali activator further improves the speed and quality of the curing reaction, so that the curing agent forms a uniform and dense cured structure in a short time, effectively enhancing the material's mechanical strength and durability.
[0122] The performance test results of the curing agents prepared in the above examples and comparative examples are shown in Table 1.
[0123] Test method:
[0124] Mechanical properties test: Tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019).
[0125] Durability test: Tested in accordance with the Concrete Quality Control Standard (GB50164-2011).
[0126] Table 1
[0127]
[0128]
[0129] It can be seen from the above that, compared with the comparative example, the embodiments of the present invention control the composition and preparation process of the curing agent so that the components cooperate with each other, effectively solve the problem of large-scale storage of fly ash and desulfurized gypsum, reduce the production cost of the curing agent, and greatly improve the tensile strength and durability of concrete, providing a green, economical, high-performance solution for the construction industry, which has broad application prospects and significant environmental benefits.
[0130] In addition, it can be seen that when all process parameters are within the preferred range of the present invention, the cement-based concrete material has better tensile strength and durability, lower cost, and is more environmentally friendly.
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A curing agent, characterized in that The raw materials include base material, mixed fiber, alkali activator and water, wherein the base material includes desulfurized gypsum, fly ash, cement and quicklime. Among the raw materials, the weight ratio of the mixed fiber to the base material is (1.2-2.4):100, and the weight ratio of the alkali activator to the base material is (8-16):100; The hybrid fiber includes glass fiber and carbon fiber; The alkaline activator includes one or more of a sodium carbonate solution, a sodium silicate solution and a sodium hydroxide solution.
2. The curing agent according to claim 1, characterized in that In the mixed fiber, The weight ratio of the glass fiber to the carbon fiber is (0.8-2):1, preferably, the weight ratio of the glass fiber to the carbon fiber is (1.2-1.6):1; and / or, The aspect ratio of the glass fiber is (100-300):1, the length of the glass fiber is 5-10 mm, and the diameter is 0.01-0.03 mm; and / or, The aspect ratio of the carbon fiber is (200-400):1, the length of the carbon fiber is 2-4 mm, and the diameter is 0.005-0.01 mm; Preferably, the glass fiber is first pretreated by one or more of heat treatment, alkali washing and surfactant treatment; more preferably, the heat treatment temperature is 400-600°C and the time is 0.5-2h; more preferably, the alkali washing is performed by one or more of sodium hydroxide solution, potassium hydroxide solution and sodium carbonate solution; more preferably, the surfactant treatment is performed by one or more of titanate coupling agent, fluorocarbon compound and polyacrylamide; Preferably, the carbon fiber is subjected to a second pretreatment by one or more of pre-oxidation, resin impregnation and acid washing; more preferably, the pre-oxidation atmosphere includes one or more of air, oxygen and ozone, the temperature is 200-400°C, and the time is 1-2.5h; more preferably, the resin impregnation is carried out with one or more of epoxy resin, polyimide resin and phenolic resin; more preferably, the acid washing is carried out with one or more of sulfuric acid, nitric acid and hydrochloric acid.
3. The curing agent according to claim 1 or 2, characterized in that The alkaline activator is a mixture of the sodium silicate solution and the sodium carbonate solution, wherein the weight ratio of sodium silicate to sodium carbonate is (0.5-2.5):1; preferably (1-2):
1.
4. The curing agent according to any one of claims 1 to 3, characterized in that The moisture content of the desulfurized gypsum is ≤15% by weight; and / or, the content of CaSO4·2H2O in the desulfurized gypsum is ≥90% by weight; and / or, Calculated by weight percentage, in the fly ash, Al2O3 accounts for 30-40%, SiO2 accounts for 45-55%, and Fe2O3 accounts for 1.5-10%.
5. The curing agent according to any one of claims 1 to 4, characterized in that The cement comprises one or more of silicate cement, sulphoaluminate cement and aluminate cement; and / or, The weight percentage of CaO in the quicklime is ≥80%; and / or the particle size of the quicklime is 50-200 μm.
6. The curing agent according to any one of claims 1 to 5, characterized in that In terms of weight percentage, in the base material, the weight ratio of the desulfurized gypsum, the fly ash, the cement and the quicklime is (25-35): (20-30): (10-20): (8-12); and / or, The weight ratio of the mixed fiber to the base material is (1.6-2):100; and / or, The weight ratio of the alkali activator to the base material is (10-15):100; and / or, The weight ratio of water to the base material is (35-55):100, preferably (40-50):
100.
7. A method for preparing the curing agent according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step S1, performing a first mixing of desulfurized gypsum, fly ash, cement, quicklime and mixed fiber to obtain a first mixture; Step S2, mixing the first mixture with water to obtain a second mixture, Step S3, performing a third mixing of the second mixture and an alkali activator to obtain the curing agent.
8. The preparation method according to claim 7, characterized in that: The first mixing speed is 600-800 rpm and the time is 2-10 min; and / or, The second mixing speed is 300-500 rpm and the time is 3-8 min; and / or, The third mixing has a rotation speed of 400 to 600 rpm and a time of 5 to 10 minutes.
9. The preparation method according to claim 7 or 8, characterized in that: Before performing step S1, the preparation method further comprises the step of drying the desulfurized gypsum until the weight percentage of water in the desulfurized gypsum is ≤5%; and / or, Before performing step S1, the preparation method further comprises grinding the fly ash until the specific surface area of the fly ash is 300 to 500 m 2 / g, particle size D90≤50μm.
10. Use of the curing agent according to any one of claims 1 to 6 in the field of construction.